RENTAL SYSTEM AND RETURN RENTAL VCD DELTA - Maksus Maksus; Sahni D. Purba, Skom, MMSI (Jurnal Sistem Informasi, 2002)
mushrooming where- man, especially Jakarta. In this business, not apart of a ministry(service) that can satisfy the customer. In scientific writing, the writer took a samplerental VCD "DELTA".In the matter to be discussed in scientific writing is to provide rental services and therapid return of vcd to members. Because during the work always be run manually,which means requiring more time for each transaction and it was not a good service.In designing a system required several design tools such as: Data Flow Diagrams(DFD) and entity relationship (ER) or often called the ERD.By using the DFD and ERD, you will see a system that is designed well, so it can beclearly understood. The database is a complete record of operational data from anorganization that is stored in an integrated manner by using certain methods in thecomputer, so that no other database systems is a computerized storage system.For that was arranged, to try to assist in providing a faster service that is by usingcomputerized.System is a group that has close relations with each other and have a function that isjointly run an attempt to achieve certain goals.